Local Treatment of a Pediatric Osteosarcoma Model with a 4-1BBL Armed Oncolytic Adenovirus Results in an Antitumor Effect and Leads to Immune Memory - Martinez-Velez, Naiara (Mol Cancer Ther, 2022)
Osteosarcoma is an aggressive bone tumor occurring primarily in pediatric patients. Despite years of intensive research, the outcomes of patients with metastatic disease or those who do not respond to therapy have remained poor and have not changed in the last 30 years. Oncolytic virotherapy is becoming a reality to treat local and metastatic tumors while maintaining a favorable safety profile. Delta-24-ACT is a replicative oncolytic adenovirus engineered to selectively target cancer cells and to potentiate immune responses through expression of the immune costimulatory ligand 4-1BB. This work aimed to assess the antisarcoma effect of Delta-24-ACT. MTS and replication assays were used to quantify the antitumor effects of Delta-24-ACT in vitro in osteosarcoma human and murine cell lines. Evaluation of the in vivo antitumor effect and immune response to Delta-24-ACT was performed in immunocompetent mice bearing the orthotopic K7M2 cell line. Immunophenotyping of the tumor microenvironment was characterized by immunohistochemistry and flow cytometry. In vitro, Delta-24-ACT killed osteosarcoma cells and triggered the production of danger signals. In vivo, local treatment with Delta-24-ACT led to antitumor effects against both the primary tumor and spontaneous metastases in a murine osteosarcoma model. Viral treatment was safe, with no noted toxicity. Delta-24-ACT significantly increased the median survival time of treated mice. Collectively, our data identify Delta-24-ACT administration as an effective and safe therapeutic strategy for patients with local and metastatic osteosarcoma. These results support clinical translation of this viral immunotherapy approach.